A Review of Membrane Distillation Process: Before, During and After Testing - N. A. S., Muhamad; N. M., Mohktar; Rosmawati, Naim; W. J., Lau; A. F., Ismail (Penerbit UMP, 2019)
Membrane Distillation (MD) is a promising technology for separation and purification processes. It is a thermally-driven separation process which allow only vapour molecules are to pass through a porous hydrophobic membrane. MD separation is driven by the vapour pressure difference existing between the porous hydrophobic membrane surfaces unlike normal membrane processes which operate on temperature difference. This paper focus on the expectation of MD treatment process primarily for the readers who have no idea about this membrane process A brief overview is given of MD before treatment process which includes membrane materials, membrane preparation techniques, membrane characteristics, module and configuration. Membrane performance during treatment process will be highlighted. Membrane fouling which is one of the major drawback of MD will be also discussed.